2015
DOI: 10.1002/cyto.a.22589
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune surveillance of central nervous system bypasses blood–brain barrier and blood–cerebrospinal–fluid barrier: Revealed with the New Marburg cerebrospinal–fluid model in healthy humans

Abstract: In healthy human brain/spinal cord, blood capillaries and venules are locked differently with junctions and basement membrane (blood-brain barrier, blood-venule barrier). In choroid plexus, epithelial tight junctions and basement membrane lock bloodcerebrospinal-fluid (CSF) barrier. Lymphocytic cell data, quantified with multicolour flow-cytometry or immuno-cytochemical methods in sample pairs of lumbar CSF, ventricular CSF and peripheral venous blood, are taken from references; similarly, data of thoracic duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 212 publications
(293 reference statements)
0
3
0
1
Order By: Relevance
“…Studies conducted on normal CSF observed that the vast majority of leucocytes is represented by central memory T lymphocytes with significantly higher percentage compared to blood. The proportion of CD56-positive cells is low while B cells are almost absent (<1%) (27)(28)(29)(30). This indicates a selective recruitment of memory T cells into normal CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on normal CSF observed that the vast majority of leucocytes is represented by central memory T lymphocytes with significantly higher percentage compared to blood. The proportion of CD56-positive cells is low while B cells are almost absent (<1%) (27)(28)(29)(30). This indicates a selective recruitment of memory T cells into normal CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte recruitment to the BBB is critical for immune surveillance of the brain . Importantly, cellular influx into the CNS also occurs during many neuroinflammatory and neurodegenerative diseases and often contributes to the pathogenesis of these disorders.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, centrifugation G-force varies from 200 g (ref. 23 ) up to 500 g (ref. 24 ), or even 1050 g (ref.…”
Section: Discussionmentioning
confidence: 99%